Genetic diversity for leaf rust resistance in durum wheat (Triticum durum) - V.G. DUBEY and S.V. SAI PRASAD, A.N. MISHRA*, K. KAUSHAL (Indian Phytopathology, 2015)
Studies were undertaken to find out the inheritance and extent of diversity for leaf rust resistance at seedling stage in four durum wheat (Triticum durum Desf.) genotypes using Puccinia triticina pathotype 12-5 (29R45). The F2and F3 analyses showed that resistance was controlled by one dominant gene each in durum genotypes ‘HD 4672’ and ‘RS 749’, and by two dominant genes each in ‘MPO 615’ and ‘Raj 6562’. Allelic tests revealed that these genes were different from each other, except one common between ‘MPO 615’ and ‘RS 749’. Thus, a total of five diverse genes for leaf rust resistance were identified among the four genotypes. The identity of the genes is not known. However, they should be different from Lr23which is common in Indian durum germplasm; and also from Lr3, Lr14a, Lr27 + Lr31, and Lr72among Lr genes reported in durum wheat, since pathotype 12-5 (29R45) is virulent to all these genes. These genotypes can contribute towards enriching diversity for leaf rust resistance in durum wheat improvement.